2001
DOI: 10.1186/cc991
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of body position strategies and respiratory therapy in paralyzed patients with acute lung injury

Abstract: Background:Routine turning of critically ill patients is a standard of care. In recent years, specialized beds that provide automated turning have been introduced. These beds have been reported to improve lung function, reduce hospital-acquired pneumonia, and facilitate secretion removal. This trial was designed to measure the physiological effects of routine turning and respiratory therapy in comparison with continuous lateral rotation (CLR).Methods:The study was a prospective, quasi-experimental, random assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 31 publications
1
24
0
6
Order By: Relevance
“…31 In this study, variations in turning did not result in differences in cardiac or pulmonary function; specifically, frequency of turning did not alter cardiac index, sputum production, or oxygenation requirements but the outcomes of interest are not specifically addressed. 31 Five related systematic reviews related to frequency of manual turning were identified during our electronic search. 2,15,[36][37][38] A sixth review, 39(p6773) written as a book chapter, also was examined.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…31 In this study, variations in turning did not result in differences in cardiac or pulmonary function; specifically, frequency of turning did not alter cardiac index, sputum production, or oxygenation requirements but the outcomes of interest are not specifically addressed. 31 Five related systematic reviews related to frequency of manual turning were identified during our electronic search. 2,15,[36][37][38] A sixth review, 39(p6773) written as a book chapter, also was examined.…”
Section: Resultsmentioning
confidence: 96%
“…In another study, 31 researchers used a quasi-experimental design with 3 arms: (1) a 2-hour manual turning regimen, (2) and (3) secretion management treatments. All patients had acute lung injury and received paralytic agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23][24][25] Our study was carried out in hemodynamically stable patients without intubation, which extends the number of patients who will benefit from rotation therapy and adds a low-cost strategy applicable in any health care center.…”
Section: Discussionmentioning
confidence: 99%
“…Kallet and colleagues demonstrated that serial measurements of deadspace could be used to monitor disease progression in ARDS [68,69]. Others have demonstrated its use in monitoring manoeuvres such as prone positioning that are designed to improve gas exchange [70,71]. Patients with ALI/ARDS that demonstrate a decrease in arterial P CO 2 i.e.…”
Section: Clinical Utilitymentioning
confidence: 99%